ROSEHIP AND ITS HEALING PROPERTIES - Pardayeva Maftuna Ilhomovna; Akbarov Nurislom Akhtamjon ugli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Rosehips containing a certain type of galactolipids have a specific anti-inflammatory effect. Rosehip Standard Powder has been formulated to maximize phytochemical retention. This powder has shown antioxidant and anti-inflammatory activity as well as clinical benefits in conditions such as osteoarthritis, rheumatoid arthritis, and inflammatory bowel disease.